Bone health in newly diagnosed female breast cancer patients in China: a cross-sectional study - Juan Wu; Xin-yu Liang; Lei Hu; Ying Li; Liang Ran; Rui-ling She; Xiu-quan Qu; Bai-qing Peng; Kai-nan Wu; Jing Wang; Ling-quan Kong (Scientific Reports)
Abstract Bone health problem is one of the important concomitant diseases of breast cancer (BC). This study aimed to investigate the bone health status of newly diagnosed female BC patients in China. A total of 636 newly diagnosed female BC patients and 268 women undergoing routine physical examinations (control group) were included. Bone mineral density and bone metabolism parameters were assessed. The association between BC and abnormal bone mass (ABM) was analyzed by logistic regression. We found that approximately 15.3% of BC patients presented with hypocalcemia after albumin adjustment. 25-OHVitD deficiency or insufficiency was observed in 92.3% of BC patients. ABM was identified in 63.2% of BC patients, comprising 36.4% with osteopenia and 26.8% with osteoporosis. ABM prevalence was significantly higher in BC patients under 40 years old (40.8%) compared to 8% in the age-matched control group. The severity of bone loss correlated with elevated bone turnover markers. Logistic regression analysis showed that a 5.5-fold and 3.4-fold increased risk of ABM and osteoporosis, respectively, in newly diagnosed BC patients versus the control group. All BC subtypes were associated with a markedly higher risk of ABM. Young BC patients (< 45 years) exhibited a nearly 9-fold higher risk of ABM compared to their age-matched counterparts. Vitamin D deficiency/insufficiency, osteopenia, and osteoporosis were highly prevalent among newly diagnosed female BC patients. Regardless of age and BC subtype, BC patients face a higher risk of ABM compared to those physical examination women, especially among the young.